Transparansi memoderasi struktur modal, perencanaan pajak, dan agresivitas pajak terhadap nilai perusahaan - Lantera, Reka Ayu; Hamdani, Hamdani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The study aims to determine the effect of transparency moderating capital structure, tax planning, and tax aggressiveness on firm value in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period for 4 years. The sampling technique used purposive sampling, and resulted in a sample size of 10 companies so that there were 40 observation samples. The data used are secondary data obtained from the Indonesia Stock Exchange website. The analysis used in this study is panel data regression. This study uses Eviews12. The results of this study indicate that: 1) Capital Structure affects Firm Value; 2) Tax Planning affects Firm Value; 3) Tax Aggressiveness affects Firm Value; 4) Transparency can moderate the relationship between Capital Structure and Firm Value; 5) Transparency can moderate the relationship between Tax Planning and Firm Value; 6) Transparency can moderate the relationship between Tax Aggressiveness and Firm Value.